2019
DOI: 10.31234/osf.io/5yru4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A chronometric model of the relationship between frontal midline theta functional connectivity and human intelligence

Abstract: Individual differences in cognitive control have been suggested to act as a domain-general bottleneck constraining performance in a variety of cognitive ability measures including but not limited to fluid intelligence, working memory capacity, and processing speed. However, due to psychometric problems associated with the measurement of individual differences in cognitive control, it has been challenging to empirically test the assumption that individual differences in cognitive control underlie individual dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In line with these ERP results, a power-spectrum analysis of EEG signals showed that phase-synchronized activity in the theta band—that is, activity associated with the facilitation of interregional goal-directed information processing—was strongly related to fluid intelligence during the P3 time window (Schubert, Hagemann, Löffler, Rummel, & Arnau, 2019). Furthermore, neuroimaging results showed that a greater integrity of white matter projections positively affected greater functional connectivity within and between brain regions, resulting in advantages in processing speed and working-memory capacity that translate into advantages in fluid intelligence (Ferrer et al, 2013; Fuhrmann, Simpson-Kent, Bathelt, the CALM Team, & Kievit, 2019; Kievit et al, 2016; Wendelken et al, 2017).…”
Section: Neural Correlates Of Domain-general Attentional Processes In...mentioning
confidence: 63%
“…In line with these ERP results, a power-spectrum analysis of EEG signals showed that phase-synchronized activity in the theta band—that is, activity associated with the facilitation of interregional goal-directed information processing—was strongly related to fluid intelligence during the P3 time window (Schubert, Hagemann, Löffler, Rummel, & Arnau, 2019). Furthermore, neuroimaging results showed that a greater integrity of white matter projections positively affected greater functional connectivity within and between brain regions, resulting in advantages in processing speed and working-memory capacity that translate into advantages in fluid intelligence (Ferrer et al, 2013; Fuhrmann, Simpson-Kent, Bathelt, the CALM Team, & Kievit, 2019; Kievit et al, 2016; Wendelken et al, 2017).…”
Section: Neural Correlates Of Domain-general Attentional Processes In...mentioning
confidence: 63%
“…The experiment started immediately after participants completed an intelligence test (data reported in Schubert et al, 2019b) and after the preparation of a 32 electrode EEG montage.…”
Section: Methodsmentioning
confidence: 99%
“…Second, neural correlates of attentional control can be recorded to dissociate attention-related neurocognitive processes from other neurocognitive processes across a wide set of different cognitive-control tasks. In fact, first results suggest that more intelligent individuals benefit from more efficient interregional goal-directed information processing, as indicated by an adaptive modulation of synchronized brain rhythms associated with attention (Schubert, Hagemann, Löffler, Rummel, & Arnau, 2019). This again supports the idea that individual differences in attentional-control processes contribute to individual differences in intelligence.…”
Section: Why Do Benefits In the Speed Of Higher-order Processing Givementioning
confidence: 99%